Museu, gestão e tecnologia: um olhar sobre as práticas museais contemporâneas - SILVA, Claudiane Diniz da (2024)
Museums, as cultural refuges, present themselves as important spaces that range from educational practices to entertainment. This work aimed to analyze museums as a space for dialogue between culture, management and technologies in order to diagnose essential elements for their functioning. Its methodology is bibliographical and exploratory research and presents relevant reflections on the modernization, interactivity and attractiveness of the museological experience as well as the difficulties encountered by public museums regarding the seasonality of the budget and the need for private museums to approach and implement the concept of a new museology . It was realized from its development that technologies are essential in museums, allowing to expand the reach and interaction with the public. They enrich exhibitions, create immersive experiences and promote accessibility. However, it is crucial to integrate them into the curatorial proposal. Furthermore, efficient management, encompassing strategic planning and resource management, is essential to ensure the proper functioning of museums, making them open, participatory and accessible spaces to society. The material was constructed in the light of Poulot (1970), which addresses issues such as expanding the public, the redefinition of museums as places of instruction and entertainment, and collecting and conservation practices in different cultural contexts; (Desvallés; Mairesse (2013) when citing museums as tangible and intangible heritage of humanity; Dutra and Faria (2017), updating the context of the work of Roger Chartier (1999), declare that it is possible to recognize the virtualization of processes in human daily life and the Brazilian Institute of Museums (2016) in subsidies for the elaboration of museological plans. Cites Milton Santos (1997) to address the context of space and memory and Yamaoka (2006) to emphasize the dissemination of information through information and communication technologies. Having In view of the research problem and the proposed objectives, two museums in São Luís do Maranhão were chosen as objects of analysis. The first is the Maranhão Historical and Artistic Museum (MHAM), public; and the one at the Vale Cultural Center (VCC MA), private. The digital world has provided a new usage model for museums, connecting people globally through the internet, videos, photos and virtual visits. This inspired research into the challenges brought by digital culture, considering the organization of museums, management models and technologies used in different types of museums.